Rule number two : lessons I learned in a combat hospital - Kraft, Heidi Squier (New York : Little, Brown and Co., 2007)
When Lt. Cmdr. Kraft's twin son and daughter were fifteen months old, she was deployed to Iraq. A clinical psychologist in the US Navy, Kraft's job was to uncover the wounds that a surgeon would never see. She put away thoughts of her children back home, acclimated to the sound of incoming rockets, and learned how to listen to the most traumatic stories a war zone has to offer. One of the toughest lessons of her deployment was perfectly articulated by the TV show M*A*S*H: "There are two rules of war. Rule number one is that young men die. Rule number two is that doctors can't change rule number one." Some Marines, Kraft realized, and even some of their doctors, would be damaged by war in ways she could not repair. And sometimes, people were repaired in ways she never expected.--From publisher description.
13 30
Keywords: Kraft, Heidi Squier; Iraq War, 2003- -- Personal narratives, American; Military psychiatry; Psychologists -- United States -- Biography; United States. -- Navy -- Women -- Biography